2014
DOI: 10.1177/2150137814527605
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring School Consultation Intervention Outcomes for Data-Based Decision Making

Abstract: School counselors increasingly are being asked to develop and implement data-based interventions for academic and social/emotional problems. The purpose of this article is to provide a demonstration of goal attainment scaling (GAS) as an intervention outcome assessment tool for school counselor's work with students. The strengths and limitations of the GAS method are described and an application is provided on the use of the method with school counseling consultation cases. We conclude that GAS is a useful too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…School counselors, for example, place a high value on using data for evaluation purposes (Hatch & Chen‐Hayes, ; Maras, Coleman, Gysbers, Herman, & Stanley, ; Young & Kaffenberger, ). Such findings are consistent with the devotion of entire practitioner‐oriented publications to data use (ASCA, ) and the extensive literature dedicated to data‐based decision making in the schools (e.g., Brady, Busse, & Lopez, ; Poynton & Carey, ).…”
supporting
confidence: 82%
“…School counselors, for example, place a high value on using data for evaluation purposes (Hatch & Chen‐Hayes, ; Maras, Coleman, Gysbers, Herman, & Stanley, ; Young & Kaffenberger, ). Such findings are consistent with the devotion of entire practitioner‐oriented publications to data use (ASCA, ) and the extensive literature dedicated to data‐based decision making in the schools (e.g., Brady, Busse, & Lopez, ; Poynton & Carey, ).…”
supporting
confidence: 82%
“…Scobbie, McLean, Dixon, Duncan, and Wyke (2013) reported that both patients and health professionals found the Goal-Action Planning model beneficial and acceptable in stroke rehabilitation. Some studies reported the use of WHO’s International Classification of Function, Disability and Health and the Talking Mats as coded guides for patient goal-setting and action planning in special communication and rehabilitation need settings (Bornman & Murphy, 2006; Murphy & Boa, 2012); and the use of Goal Attainment Scaling as an effective framework for the evaluation of the achievement of treatment goals (Balkin, 2013; Brady, Busse, & Lopez, 2014). Another two goal-setting frameworks reported in healthcare improvement planning are total quality management and continuous quality improvement initiatives (Ginsburg, 2001; Parker, 2003; Medlin & Green, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Goal attainment scaling (GAS) can serve as a socially and educationally valid method to augment trend analysis. GAS has been put forward as a reliable and valid criterion-referenced approach that can be readily applied to monitoring IEP outcomes in practice settings, including special education (Roach & Elliott, 2005) and the related fields of school counseling (Brady et al, 2014;McGill et al, 2016) and school psychology (Busse et al, 2015;Coffee & Ray-Subramanian, 2009). The GAS method was developed by Kiresuk and Sherman (1968) and further explicated by Kiresuk et al (1994) to evaluate treatment outcomes from mental health services.…”
Section: Goal Attainment Scalingmentioning
confidence: 99%